MULTIPLE-COURSE PHOTODYNAMIC THERAPY FOR VERRUCOUS LEUKOPLAKIA OF MUCOUS MEMBRANE OF BODY OF THE TONGUE (CASE REPORT) - Yu. P. Istomin; T. P. Artemyeva; D. A. Tzerkovsky (Biomedical Photonics, 2016)
The results of treatment of the patient with verrucous luekoplakia of mucous membrane of body of the tongue with photodynamic therapy are represented. In 2015 the patient underwent 4 courses of photodynamic therapy with photosensitizer photolon. Photolon was injected at dose of 2 mg/kg 3 h before irradiation (laser output power was 0.262 W, light dose – 50 and 100 J/cm2). The result of treatment was assessed as complete regression: 4 months after multiple-course photodynamic therapy there were no clinical and histological signs of luekoplakia.